ANALISIS NILAI KEBANGSAAN PADA GENERASI-Z DI KOTA MEDAN - Romadhona, M. Rifqi; Makmur, Chesa Syaqira; Monica, Eka Syafrina; Sukartara, Nirwansyah; Lubis, Hamidah Azzahra S (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
National characteristic is an important component in the development of a strong nation. National characteristic primarily impacts the increase of affection for the country and can be a motivator in warding off dangers. Generation Z is sometimes regarded as a generation that has witnessed quick technological advancements, therefore it is not uncommon for them to be less aware of the value of National Value in the context of national life. The purpose of this study is to investigate the extent to which the z-generation in Medan feels a sense of nationality. In its hunt for data, this study uses qualitative methodologies. The results of this study lead to the z-generation in Medan city having a very good feeling of national value while being faced with numerous difficulties of the globalization effect.